ANXIOUS AND AGGRESSIVE: THE CO‐OCCURRENCE OF IED WITH ANXIETY DISORDERS. Issue 2 (30th September 2015) - Keyes, Katherine M.; McLaughlin, Katie A.; Vo, Thomas; Galbraith, Todd; Heimberg, Richard G.
Abstract : Background: Evidence suggests that impulsive aggression and explosive anger are common among individuals with anxiety disorders; yet, the influence of intermittent explosive disorder (IED) on the onset, course, consequences, and patterns of comorbidity among those with anxiety disorders is unknown. Methods: Data were drawn from the National Comorbidity Survey Replication ( N = 9, 282) and Adolescent Supplement ( N = 9, 632), nationally representative surveys conducted between 2001 and 2004. Diagnoses were based on structured lay‐administered interviews. Lifetime diagnoses were assessed with structured instruments. Outcomes included comorbidity, functional and role impairment, and treatment utilization. Results: Adolescents with a lifetime anxiety disorder had a higher prevalence of a lifetime anger attacks (68.5%) and IED (22.9%) than adolescents without a lifetime anxiety disorder (48.6 and 7.8%, respectively), especially social phobia and panic disorders. Similar elevation was found for adults. Age of onset and course of anxiety disorders did not differ by IED. Severe functional impairment associated with anxiety was higher among adolescents (39.3%) and adults (45.7%) with IED than those without IED (29.2 and 28.2%, respectively). Comorbidity for all other disorders was elevated. However, individuals with anxiety disorders and IED were no more likely to use treatment services than those with anxiety disorders without IED. Conclusions: Individuals with IED concomitant to anxiety disorder, especially social phobia and panic, are at marked risk for worse functional impairment and a higher burden of comorbidity, but onset and course of anxiety disorder do not differ, and those with anxiety and IED are no more likely to utilize treatment services. Assessment, identification, and specialized treatment of anger in the context of anxiety disorders are critical to reducing burden.